Preparation method of silver selenide self-supporting flexible thermoelectric film
Through screen printing-annealing strategy and polydimethylsiloxane filling holes, the substrate-free problem in the preparation of silver selenide self-supported flexible film is solved, and the Ag2Se film with high flexibility and excellent thermoelectric properties is achieved, improving the The stability and thermoelectric properties of the device are achieved.
Patent Information
- Application Number
- CN202411295232.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-17
- Publication Date
- 2024-12-20
AI Technical Summary
The prior art is difficult to prepare a substrateless silver selenide self-supporting flexible film, resulting in a weak bonding force between the material and the substrate limiting the deformation capability and stability of the flexible device.
Using screen printing-annealing strategy, a porous structure was introduced, and the thermoelectric performance was optimized by regulating the annealing temperature and pore density, and the holes were filled with polydimethylsiloxane (PDMS), and the Ag2Se inorganic conductive network-PDMS organic frame structure was constructed to realize the Preparation of substrateless Ag2Se flexible film.
The substrate-free, self-supported, completely inorganic Ag2Se flexible film was successfully obtained, which improved the flexibility and thermoelectric properties of the film, improved the bending cycle stability and conductivity retention rate, and was able to work effectively on complex shape heat sources.
Smart Images

Figure CN119173122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermoelectric energy conversion materials, and in particular relates to a method for preparing a silver selenide self-supporting flexible thermoelectric film. Background Art
[0002] In recent years, with the rapid development of electronic devices in the field of wearable technology and the Internet of Things, flexible thermoelectric generators (f-TEGs) assembled with flexible thermoelectric films can directly and sustainably convert low-grade waste heat (such as body heat) into electrical energy, which is expected to be used for powering wearable electronic devices, etc., and has attracted widespread attention from researchers. The energy conversion efficiency of f-TEG is determined by the dimensionless thermoelectric figure of merit (zT) of the membrane material, zT = S 2 σT / κ, where S is the Seebeck coefficient, σ is the electrical conductivity, T is the absolute temperature, and κ is the total thermal conductivity. 2 σ is the thermoelectric power factor, which can be used to evaluate the electrical output performance of the thermoelectric film. The thermoelectric film used in flexible thermoelectric devices needs to have not only high thermoelectric performance, but also good flexibility (such as being able to bend, twist and stretch), so that the device can better fit the complex shape of the heat source and avoid damage during long-term service. Therefore, the development of thermoelectric films with excellent thermoelectric performance and flexibility is crucial for the practical application of flexible thermoelectric devices.
[0003] The n-type semiconductor silver selenide (Ag2Se) has a narrow band gap, high carrier mobility and low lattice thermal conductivity, and shows good application prospects in near-room temperature thermoelectric performance. In recent years, in addition to being used as a bulk thermoelectric material, Ag2Se is also often used as a flexible thermoelectric film, which is a hot topic in the research field of wearable thermoelectric devices. Limited by low flexibility and plasticity, Ag2Se is difficult to exist independently in the form of a self-supporting flexible film. Therefore, researchers at home and abroad usually use Ag2Se materials combined with organic flexible substrates to prepare flexible thermoelectric films. However, the films obtained by this method have certain disadvantages: additional substrates are required when preparing flexible thermoelectric devices (for example, Ag2Se@nylon composite films are pasted on polyimide substrates to obtain devices), which may reduce the utilization rate of heat from the heat source; the weak bonding force between the material and the substrate limits its deformation ability, which may affect the stability of the flexible device during use. Therefore, finding a suitable method to prepare a substrate-free Ag2Se self-supporting flexible film is the key and difficulty in promoting the application of Ag2Se-based thermoelectric films. Summary of the invention
[0004] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is: how to prepare a substrate-free silver selenide self-supporting flexible film.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solution: a method for preparing a silver selenide self-supporting flexible thermoelectric film, comprising the following steps:
[0006] S1: Grind silver selenide (Ag2Se) powder, pineneol and dispersant DISPERBYK-110 in a mortar for 0.5 to 2 hours to fully mix them. The mass parts of silver selenide powder are 50 to 1000 parts, the mass parts of pineneol are 5 to 100 parts, and the volume parts of dispersant are 10 to 500 parts; the mass units of Ag2Se and pineneol are mg, and the volume unit of dispersant is μL.
[0007] S2: The mixture in S1 is passed through a printing screen with a mesh size of 50 to 500 and is evenly printed on a polyimide (PI) film with a thickness of 0.05 to 0.2 mm to obtain an Ag2Se ink@PI composite film.
[0008] S3: The Ag2Se ink@PI composite film in S2 is placed in a tubular furnace and kept at 200-500°C for 0.5-4h. After cooling, the Ag2Se film can be peeled off from the PI substrate to obtain a substrate-free silver selenide self-supporting film.
[0009] S4: Place polydimethylsiloxane (PDMS) and a curing agent in a flask and stir for 0.5 to 2 hours to mix them evenly, wherein the mass ratio of PDMS to the curing agent is 7 to 14:1. The mass units of polydimethylsiloxane PDMS and the curing agent are both g.
[0010] S5: Spread the mixture obtained in S4 on the surface of the substrate-free Ag2Se film obtained in S3, wait for 10 to 30 minutes, and then transfer the whole mixture to a vacuum drying oven for full curing to obtain an Ag2Se / PDMS film. The curing temperature is 50 to 100°C and the curing time is 24 to 48 hours.
[0011] Furthermore, the mass volume ratio of the silver selenide powder, pineol and dispersant DISPERBYK-110 is 4:1:2, the mass ratio of polydimethylsiloxane and curing agent is 10:1, the grinding time is 0.5h, the mesh size is 200 mesh, the PI substrate thickness is 0.15mm, the annealing temperature and time are 400°C and 2h respectively, the mass ratio of polydimethylsiloxane and curing agent is 10:1, the waiting time after tiling is 30min, and the curing temperature and time are 100°C and 24h respectively.
[0012] A silver selenide self-supporting flexible thermoelectric film is obtained by adopting the preparation method of the silver selenide self-supporting flexible thermoelectric film.
[0013] In the present invention, a screen printing-annealing strategy is adopted to successfully introduce a porous structure into the Ag2Se film, so that it can exist independently from the substrate, and its thermoelectric performance is optimized by regulating the annealing temperature or adjusting the pore density. By regulating the thickness of the self-supporting flexible film combined with the regulation of the pore density, it has good flexibility. Further, polydimethylsiloxane (PDMS) is infiltrated into the pore structure of the Ag2Se film, and a special structure of the Ag2Se inorganic conductive network-PDMS organic framework is controllably constructed, so that the Ag2Se-based thermoelectric film has excellent flexibility.
[0014] (1) Using a facile, efficient, controllable, and scalable strategy, a porous structure with adjustable pore density was constructed in the membrane to obtain a substrate-free, self-supporting, all-inorganic Ag2Se flexible membrane.
[0015] (2) The flexibility and thermoelectric properties of the Ag2Se film were optimized by adjusting experimental parameters such as the morphology of Ag2Se powder, the annealing temperature of the sample, and the mesh size of the printing screen.
[0016] (3) A special composite structure of Ag2Se inorganic conductive network-PDMS organic framework was constructed, which further improved the flexibility of the thermoelectric film.
[0017] Compared with the prior art, the present invention has at least the following advantages:
[0018] 1. In order to solve the problems existing in the preparation of membranes by combining inorganic non-flexible thermoelectric materials with organic flexible substrates (for example, the weak bonding force between the material and the substrate limits its deformation ability), the present invention uses Ag2Se powder synthesized by solution chemical synthesis or ball milling as the raw material for preparing membrane materials, develops a screen printing-annealing strategy, introduces a porous structure, and realizes the preparation of Ag2Se flexible membranes without substrates. The effect of high-density pore structures on improving the flexibility of silver selenide membranes has not been reported before.
[0019] 2. The carrier concentration was regulated by changing the annealing temperature, and the power factor of the silver selenide thermoelectric film was optimized. The power factor of the film prepared with solution-synthesized Ag2Se powder as raw material was 670 μW m at 375 K. -1 K -2 , and after the film was repeatedly bent 1000 times with a radius of 4 mm, its conductivity only decreased by about 4%.
[0020] 3. By changing the screen-printed Ag2Se material from particles to nanowires, the pore density of the Ag2Se thermoelectric film can be controlled. The corresponding Ag2Se self-supporting thermoelectric film has a power factor of 1240 μW m at 308 K. -1 K -2 .
[0021] 4. By cleverly utilizing the pore structure of the Ag2Se porous membrane, a special structure of Ag2Se inorganic conductive network-PDMS organic skeleton was further constructed. This structure has not been reported in the silver selenide system. This strategy improves the bending cycle stability of the membrane. The Ag2Se / PDMS membrane can be repeatedly bent 1000 times with a radius of 4mm without a significant decrease in conductivity, and can be wrapped around a cylinder with a radius of 1mm without damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Figure a is a physical photograph of the Ag2Se self-supporting film without substrate; Figure b is a surface SEM image of the Ag2Se self-supporting film without substrate; Figure c is a cross-sectional SEM image of the Ag2Se film printed by a 60-mesh screen; Figure d is a cross-sectional SEM image of the Ag2Se film printed by a 200-mesh screen; Figure e is a bending photo of the Ag2Se film printed by a 60-mesh screen; Figure f is a bending photo of the film printed by a 200-mesh screen.
[0023] Figure 2 : Figure a shows the conductivity retention rate of the substrate-free Ag2Se self-supporting film after 1000 bending cycles with a radius of 4 mm; Figure b shows the power factor variation curve of the Ag2Se thermoelectric film prepared after annealing at different temperatures (z; unit is K).
[0024] Figure 3 : a is a real photo of the Ag2Se / PDMS membrane; Figure b is the conductivity retention rate of the Ag2Se / PDMS membrane after 2000 bending cycles with a radius of 4 mm.
[0025] Figure 4 The figure is a simplified flow chart of the method of the present invention. DETAILED DESCRIPTION
[0026] The present invention is described in further detail below.
[0027] At present, various membrane material preparation methods such as magnetron sputtering, vacuum assisted filtration, and screen printing usually combine Ag2Se with a flexible substrate or directly prepare an Ag2Se film on a flexible substrate to obtain an Ag2Se film with certain flexibility. Although most of these Ag2Se films show good thermoelectric properties, the weak combination and flexibility mismatch between the flexible substrate and the Ag2Se material cause a considerable loss of thermoelectric performance during its repeated deformation (such as bending). In addition, since Ag2Se has low flexibility and plasticity, it is difficult for Ag2Se to exist in the form of a self-supporting flexible film. The present invention introduces a porous structure inside the Ag2Se film. When the film is bent, the high-density holes can effectively release the stress during the bending process, avoid crack generation and film breakage, and significantly improve the flexibility of the film, so that it can also obtain good flexibility without a flexible substrate. The present invention cleverly utilizes the porous structure of the Ag2Se membrane and further fills these holes with polydimethylsiloxane (PDMS) to form a special sandwich structure. The excellent flexibility of PDMS further stabilizes the microstructure of the Ag2Se membrane without affecting the thermoelectric properties of the Ag2Se membrane, thereby making the Ag2Se / PDMS membrane as a whole show higher conductivity bending cycle stability.
[0028] (1) There is no effective strategy to introduce pore structure into Ag2Se thermoelectric films to make them self-supporting and flexible;
[0029] (2) There is no controllable preparation strategy for Ag2Se self-supporting flexible thermoelectric films with co-adjustable shape and size;
[0030] (3) There is no effective strategy to controllably construct the special structure of Ag2Se inorganic conductive network-PDMS organic framework, which can achieve the excellent flexibility of Ag2Se-based thermoelectric films.
[0031] The present invention realizes the controllable preparation of substrate-free Ag2Se self-supporting flexible thermoelectric film materials, optimizes the flexibility and thermoelectric performance of the film by adjusting the experimental parameters, and finally constructs a composite structure of Ag2Se inorganic conductive network structure-PDMS organic framework to obtain excellent flexibility: ① By adjusting the ratio of Ag2Se, pineol and DISPERBYK-110, the viscosity and leveling of the Ag2Se ink are in a suitable range (for example, when the pineol content is too low, the viscosity of the corresponding ink is high and the leveling is poor), so that the thickness of the printed film is uniform, and the size and shape of the film can be effectively adjusted. ② Through the annealing process, organic matter can be effectively removed, so that organic matter with low conductivity is removed, and Ag2Se particles are in contact with each other but not fully densified, so that the film presents a porous microstructure, thereby achieving stable self-support and good flexibility. ③ Controlling the annealing temperature and time can regulate the Ag:Se ratio in Ag2Se, which effectively optimizes the thermoelectric power factor. For example, adjusting the annealing temperature can control the volatilization of Se elements in the Ag2Se film to a certain extent. The higher the temperature, the more Se volatilizes. According to semiconductor-related theories, for n-type semiconductor Ag2Se, when the Se element content decreases, the carrier concentration of the material will increase, which will achieve the regulation of thermoelectric performance. ④ By adjusting the mesh number of the printing screen, the Ag2Se ink per unit area is different, thereby changing the thickness of the substrate-free Ag2Se film. The thickness directly affects its flexibility. The thinner the film, the higher the flexibility. For example, the larger the mesh number, the less Ag2Se ink passes through the screen, and the thinner the thickness of the prepared film, which helps the Ag2Se film to obtain better flexibility. ⑤ Compared with the film prepared with nanoparticles as raw materials, the Ag2Se film prepared with Ag2Se nanowires as raw materials has a relatively small density of pores, which helps the film to obtain higher carrier mobility and power factor. ⑥ Control the ratio of PDMS and curing agent so that its viscosity and hardness after curing are in an optimal range, so that the flexibility of the Ag2Se porous membrane and the excellent flexibility of PDMS can be fully utilized, so that the Ag2Se / PDMS membrane has excellent flexibility.
[0032] A method for preparing a silver selenide self-supporting flexible thermoelectric film, the specific steps are as follows:
[0033] S1: 50-1000 mg of Ag2Se powder (can be particles, the same as the synthesis method in the previous patent, or prepared by ball milling; can be nanowires, the process can be adjusted and the material synthesis can be carried out according to the literature report), 5-100 mg of pinene alcohol and 10-500 μL DISPERBYK-110 (dispersant) is ground in a mortar for 0.5 to 2 hours to make it fully mixed; specifically, the added amount of the Ag2Se powder can be 50 mg, 100 mg, 300 mg, 600 mg, 900 mg or 1000 mg, the added amount of the pineneol can be 5 mg, 25 mg, 45 mg, 65 mg, 85 mg or 100 mg, the added amount of the DISPERBYK-110 can be 10 μL, 100 μL, 200 μL, 300 μL, 400 μL or 500 μL, and the grinding time can be 0.5 h, 1 h, 1.5 h or 2 h.
[0034] S2: The above mixture is evenly printed on a polyimide (PI) film with a thickness of 0.05 to 0.2 mm through a printing screen with a mesh number of 50 to 500 to obtain an Ag2Se ink @ PI composite film; the mesh number can be 50 mesh, 100 mesh, 200 mesh, 300 mesh, 400 mesh or 500 mesh, and specifically, the thickness can be 0.05 mm, 0.1 mm, 0.15 mm or 0.2 mm.
[0035] S3: The Ag2Se ink@PI composite film is placed in a tubular furnace and kept at 200-500°C for 0.5-4h. After cooling, the Ag2Se film can be peeled off from the PI substrate to obtain an Ag2Se substrate-free film. The temperature can be 200°C, 300°C, 400°C or 500°C, and the time can be 0.5h, 1h, 2h, 3h or 4h.
[0036] S4: 2-8g PDMS and 0.2-0.8g curing agent are placed in a flask and stirred for 0.5-2h to mix them evenly. The PDMS content can be 2g, 4g, 6g or 8g, and specifically, the curing agent content can be 0.2g, 0.4g, 0.6g or 0.8g, and the stirring time can be 0.5h, 1h, 1.5h or 2h.
[0037] S5: Spread the mixture obtained in S4 on the surface of the substrate-free Ag2Se film obtained in step S3, wait for 10 to 30 minutes, and then transfer the whole mixture to a vacuum drying oven for full curing to obtain an Ag2Se / PDMS film. The curing temperature is 50 to 100°C, and the curing time is 24 to 48 hours. Specifically, the waiting time can be 10 minutes, 20 minutes or 30 minutes, the curing temperature can be 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, and the curing time can be 24 hours, 36 hours or 48 hours.
[0038] Example 1: Preparation of a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using solution-synthesized Ag2Se submicron particles as raw materials, 200 mesh screen printing, and annealing at 400°C. The specific steps are as follows:
[0039] 1) Grind 100 mg of Ag2Se submicron particles, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar.
[0040] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 200-mesh screen;
[0041] 3) placing the Ag2Se ink@PI composite film in a tube furnace and annealing it at 400°C for 2h, and then peeling the Ag2Se film from the PI substrate after cooling;
[0042] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0043] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0044] Example 2: The specific steps for preparing a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using solution-synthesized Ag2Se submicron particles as raw materials, 60 mesh screen printing, and 400°C annealing are as follows:
[0045] 1) Grind 100 mg of Ag2Se submicron particles, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar.
[0046] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 60-mesh screen;
[0047] 3) placing the Ag2Se ink@PI composite film in a tube furnace and annealing it at 400°C for 2h, and then peeling the Ag2Se film from the PI substrate after cooling;
[0048] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0049] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0050] Example 3: Preparation of a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using solution-synthesized Ag2Se submicron particles as raw materials, 200 mesh screen printing, and 300°C annealing. The specific steps are as follows:
[0051] 1) Grind 100 mg of Ag2Se submicron particles, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar.
[0052] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 200-mesh screen;
[0053] 3) placing the Ag2Se ink@PI composite film in a tube furnace and annealing it at 300°C for 2h, and then peeling the Ag2Se film from the PI substrate after cooling;
[0054] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0055] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0056] Example 4: Preparation of a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using solution-synthesized Ag2Se submicron particles as raw materials, 200 mesh screen printing, and 500°C annealing. The specific steps are as follows:
[0057] 1) Grind 100 mg of Ag2Se submicron particles, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar.
[0058] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 200-mesh screen;
[0059] 3) The Ag2Se ink@PI composite film is placed in a tube furnace and annealed at 500°C for 2h. After cooling, the Ag2Se film can be peeled off from the PI substrate;
[0060] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0061] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0062] Example 5: The specific steps for preparing a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using solution-synthesized Ag2Se nanowires as raw materials, 200 mesh screen printing, and annealing at 400°C are as follows:
[0063] 1) Grind 100 mg of Ag2Se nanowires, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar.
[0064] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 200-mesh screen;
[0065] 3) placing the Ag2Se ink@PI composite film in a tube furnace and annealing it at 400°C for 2h, and then peeling the Ag2Se film from the PI substrate after cooling;
[0066] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0067] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0068] Example 6: The specific steps for preparing a substrate-free Ag2Se self-supporting flexible film and a corresponding Ag2Se / PDMS flexible film using Ag2Se powder prepared by ball milling as a raw material, 200 mesh screen printing, and annealing at 400° C. are as follows:
[0069] 1) Grind 100 mg of Ag2Se powder prepared by ball milling, 25 mg of terpineol and 50 μL of DISPERBYK-110 in a mortar and evenly;
[0070] 2) printing the mixture on a PI film with a thickness of 0.15 mm through a 200-mesh screen;
[0071] 3) placing the Ag2Se ink@PI composite film in a tube furnace and annealing it at 400°C for 2h, and then peeling the Ag2Se film from the PI substrate after cooling;
[0072] 4) Place 4 g of PDMS and 0.4 g of curing agent in a flask and stir for 1 h to mix them evenly;
[0073] 5) The above mixture was spread on the surface of the substrate-free Ag2Se film obtained in step (4), and after waiting for 20 minutes, the whole mixture was transferred to a vacuum drying oven at 100°C for full curing for 24 hours.
[0074] Figure 1 a is an appearance picture of the substrate-free Ag2Se film (prepared in the first four steps of Example 1), showing its self-supporting characteristics, and its shape and size can be effectively adjusted. Figure 1 b is the SEM image of the Ag2Se film, showing its porous structure. Figure 1 The cross-sectional SEM images of Ag2Se films (prepared in the first four steps of Example 2 and Example 1, respectively) prepared by printing at screen mesh sizes of 60 and 200, respectively, show that the higher the printing mesh size, the thinner the film. Figure 1 ef shows the minimum bending radius that the above film can withstand. It can be seen that the thinner the film, the smaller the bending radius it can withstand without being damaged.
[0075] Figure 2 a shows the conductivity retention of the substrate-free Ag2Se porous membrane (prepared in the first four steps of Example 1) after 1000 bending cycles with a radius of 4 mm, indicating that its conductivity is only reduced by 4%. Figure 2 b shows the effect of different annealing temperatures on the power factor of the Ag2Se films (prepared in the first four steps of Examples 1, 3, and 4, respectively). The results show that the samples annealed at 400 °C obtained the largest power factor in the test temperature range, with a maximum value of 670 μW m at 375 K. -1 K -2 .
[0076] Figure 3 a shows the appearance of the Ag2Se / PDMS film (Example 1), indicating that it has good flexibility. Figure 3 b shows the conductivity retention of the Ag2Se / PDMS membrane after 1000 bending cycles with a radius of 4 mm, showing that its conductivity remains almost unchanged, indicating that constructing this special composite structure helps to achieve excellent flexibility.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a silver selenide self-supporting flexible thermoelectric film, characterized in that: The steps include: S1: Grind the silver selenide powder, pinene alcohol and dispersant DISPERBYK-110 in a mortar for 0.5 to 2 hours to fully mix them. Parts by mass of silver selenide powder: 50 to 1000 parts; The mass proportion of terpineol: 5 to 100 parts; The volume proportion of the dispersant is: 10 to 500 parts; S2: The mixture in S1 is passed through a printing screen with a mesh size of 50 to 500 meshes and evenly printed on a polyimide film with a thickness of 0.05 to 0.2 mm to obtain an Ag2Se ink@PI composite film; S3: placing the Ag2Se ink@PI composite film in S2 in a tube furnace and keeping it at 200-500°C for 0.5-4h, and after cooling, peeling the Ag2Se film from the PI substrate to obtain a substrate-free silver selenide self-supporting film; S4: placing polydimethylsiloxane and a curing agent in a flask and stirring for 0.5 to 2 hours to mix them evenly, wherein the mass ratio of polydimethylsiloxane to the curing agent is 7 to 14:1; S5: Spread the mixture obtained in S4 on the surface of the substrate-free Ag2Se film obtained in S3, wait for 10 to 30 minutes, and then transfer the whole mixture to a vacuum drying oven for full curing to obtain an Ag2Se / PDMS film. The curing temperature is 50 to 100°C and the curing time is 24 to 48 hours.
2. The method for preparing a silver selenide self-supporting flexible thermoelectric film according to claim 1, characterized in that: The mass volume ratio of the silver selenide powder, pineol and dispersant DISPERBYK-110 is 4:1:2, the mass ratio of polydimethylsiloxane to curing agent is 10:1, the grinding time is 0.5h, the mesh size is 200 mesh, the PI substrate thickness is 0.15mm, the annealing temperature and time are 400°C and 2h respectively, the mass ratio of polydimethylsiloxane to curing agent is 10:1, the waiting time after tiling is 30min, and the curing temperature and time are 100°C and 24h respectively.
3. A silver selenide self-supporting flexible thermoelectric film, characterized in that: Obtained by the preparation method of a silver selenide self-supporting flexible thermoelectric film as described in claim 1 or 2.
